Not all COVID-19 pandemic waves are alike. (July 2021) - Domingo, Pere; Pomar, Virgina; Mur, Isabel; Castellví, Ivan; Corominas, Héctor; de Benito, Natividad
Abstract: Objective: We aimed to assess differences in patients' profiles in the first two surges of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic in Barcelona, Spain. Methods: We prospectively collected data from all adult patients with SARS-CoV-2 infection diagnosed at the Hospital de la Santa Creu i Sant Pau, Barcelona, Spain. All the patients were diagnosed through nasopharyngeal swab PCR. The first surge spanned from 1st March to 13th August 2020, while surge two spanned from 14th August to 8th December 2020. Results: There were 2479 and 852 patients with microbiologically proven SARS-CoV-2 infection in surges one and two, respectively. Patients from surge two were significantly younger (median age 52 (IQR 35) versus 59 (40) years, respectively, p < 0.001), had fewer comorbidities (379/852, 44.5% versus 1237/2479, 49.9%, p 0.007), and there was a shorter interval between onset of symptoms and diagnosis (median 3 (5) versus 4 (5) days, p < 0.001). All-cause in-hospital mortality significantly decreased for both the whole population (24/852, 2.8% versus 218/2479, 8.8%, p < 0.001) and hospitalized patients (20/302, 6.6% versus 206/1570, 13.1%, p 0.012). At adjusted logistic regression analysis, predictors of in-hospital mortality were older age (per year, adjusted odds ratio (aOR) 1.079, 95%CI 1.063–1.094), male sex (aOR 1.476, 95%CI 1.079–2.018), having comorbidities (aOR 1.414, 95%CI 0.934–2.141), ICU admission (aOR 3.812, 95%CI 1.875–7.751), mechanical ventilation (aOR 2.076, 95%CI 0.968–4.454), and coronavirus disease 2019 (COVID-19) during surge one (with respect to surge two) (aOR 2.176, 95%CI 1.286–3.680). Conclusions: First-wave SARS-CoV-2-infected patients had a more than two-fold higher in-hospital mortality than second-wave patients. The causes are likely multifactorial.